Their own devices. (Economist, 2015)
The article focuses on computer security and the internet of things (IoT). It comments that security researchers and hackers have demonstrated it is possible to hack into and control computerized medical devices and mentions in 2011 computer researcher Jay Radcliffe demonstrated how to remotely disable insulin pumps. It talks about the vulnerability of automobiles by hacking into them and speculates on the creation of botnets using the IoT. It considers the lack of computer security in the IoT.